2009
DOI: 10.1063/1.3242339
|View full text |Cite
|
Sign up to set email alerts
|

Development of high critical current density in multifilamentary round-wire Bi2Sr2CaCu2O8+δ by strong overdoping

Abstract: Abstract:Bi 2 Sr 2 CaCu 2 O 8+δ is the only cuprate superconductor that can be made into a round-wire conductor form with a high enough critical current density J c for applications. Here we show that the J c (5 T,4.2 K) of such Ag-sheathed filamentary wires can be doubled to more than 1.4 × 10 5 A/cm 2 by low temperature oxygenation. Careful analysis shows that the improved performance is associated with a 12 K reduction in transition temperature T c to 80 K and a significant enhancement in intergranular conn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…Figure 8 shows this using FIBed transverse cross-sectional images at four different locations in the same filament from a 27-FP wire. Figure 8(a) shows an almost 100% dense microstructure, meaning that the I c of this section is dependent principally on the grain boundary properties, which can be significantly ameliorated by overdoping [12]. However, the three other images reveal porous structures inside the filament, the worst case being shown in figure 8(d) where the filament is a hollow shell, greatly suppressing connectivity by reduction of physical grain-to-grain connections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 8 shows this using FIBed transverse cross-sectional images at four different locations in the same filament from a 27-FP wire. Figure 8(a) shows an almost 100% dense microstructure, meaning that the I c of this section is dependent principally on the grain boundary properties, which can be significantly ameliorated by overdoping [12]. However, the three other images reveal porous structures inside the filament, the worst case being shown in figure 8(d) where the filament is a hollow shell, greatly suppressing connectivity by reduction of physical grain-to-grain connections.…”
Section: Discussionmentioning
confidence: 97%
“…It appears that the superconducting connectivity was also enhanced because J c increased significantly. Varying the cooling rate did not vary the flux pinning and thus had no effect on J c , since the irreversibility field H irr , evaluated by the extrapolated Kramer field H K , was the same for all samples after they received a full, final oxygenation that put the 2212 grains into a reproducible, overdoped state [12].…”
Section: Introductionmentioning
confidence: 99%
“…The upper limit to the critical current density (J c ), normally defined by I c /A sc (I c is the critical current and A sc is the superconducting cross-sectional area) is always determined by vortex pinning, but the meaning of J c defined in this way is only very uncertainly connected to the vortex-pinning limit if A sc varies locally. Extensive recent analysis of J c of Bi-2212 wires concludes that vortex pinning is optimized by a final low-temperature heat treatment (HT) in pure O 2 that overdopes the Bi-2212, raises the irreversibility field (H irr ), and reduces the electronic anisotropy [5]. The J c of typical wires is also enhanced by slow cooling through the resolidification step that follows melting of the Bi-2212 filament bundles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the weakened intergrain connections after sintering, the increasing critical current density should be attributed to the doping effect on Bi-2212 phase. It is reported that the fabrication of overdoping Bi-2212 superconductors with oxygenation treatments could enhance the current capacity [35]. Thus, in this study, hole doping Li and K both can tune superconductors into overdoping region, thus lead to the enhancement of current capacity.…”
Section: Resultsmentioning
confidence: 68%